How stressful are economic competitions in the lab?: An investigation with physiological measures - Buckert, Magdalena; Schwieren, Christiane; Fiebach, Christian (Journal of economic psychology, 2017)
Competition is ubiquitous in economic life. Yet, negative consequences of competitive environments have been reported and everyday experience suggests that competitive situations can be very stressful. It is, however, an open question whether or not economic competitions in the laboratory indeed elicit physiological stress reactions. Our study examined subjectively perceived stress and physiological changes induced by a well-established economic laboratory competition paradigm (first used in Niederle & Vesterlund, 2007) in a mixed-gender sample of 111 healthy participants. A mental arithmetic task was performed first under a piece rate (i.e., non-competitive) payment scheme and afterwards under a tournament condition. In a third round, participants decided how to be paid (i.e., piece rate or tournament). Our results indicate that compared to a control group, which performed only the non-competitive condition, the competitive game condition elicited subjective and physiological reactions that are indicative of mild stress, i.e., an increase in heart rate and a decrease of calmness and mood. Furthermore, reactions that are thought to reflect an active coping style were related to the self-selection into competition in the third round of the game. We speculate that real-life economic competitions might be even stronger stressors and the way how people cope with this kind of stress might be related to competitiveness in real-life economic contexts.